Controlling the local extracellular electric field can suppress the generation and propagation of seizures and spikes in the hippocampus - Muthumeenakshi Subramanian; Chia-Chu Chiang; Cedric Levi; Dominique M. Durand (Brain Stimulation)
Objective: Neural activity such as theta waves, epileptic spikes and seizures can cross a physical transection using electric fields thus propagating by ephaptic coupling and independently of synaptic transmission. Recruitment of neurons in epilepsy occurs in part due to electric field coupling in addition to synaptic mechanisms. Hence, controlling the local electric field could suppress or cancel the generation of these epileptic events. Methods: 4-aminopyridine (4-AP) was used to induce spontaneous epileptic spikes and seizures in longitudinal hippocampal slices in-vitro. Two extracellular recording electrodes were placed in the tissue, one at the edge of the slice on the temporal side at the focus of the epileptic activity and the other on the septal side to record the propagation. Two stimulating electrodes were placed outside the slice at the edge of the focal zone. An extracellular voltage clamp circuit maintained the voltage within the focus at 0V with respect to the bath ground. Results: Experiments showed that 100 % of the epileptic activity originated at the temporal region and propagated to the septal region of the slices thereby establishing the existence of a focus in the temporal end of the tissue. The clamp achieved 100 % suppression of all seizure activity in the tissue with current amplitudes between 70 and 250 nA. No spikes or seizures were observed in either the focus or the septal region when the clamp was “on”. When the clamp was turned off, both the spikes and seizure events recovered immediately. Conclusions: The experiments show that controlling the extracellular voltage within a focus can prevent the generation and the propagation of epileptiform activity from the focus with very low amplitudes currents.